Patient Wellbeing and Quality of Life After Nasoseptal Flap Closure for Endoscopic Skull Base Reconstruction. (April 2020) - Castle-Kirszbaum, Mendel; Wang, Yi Yuen; King, James; Uren, Brent; Dixon, Ben; Zhao, Yi Chen; Lim, Kai-Zheong; Goldschlager, Tony
Highlights: The NSF is the preferred method for closing large skull base defects. NSF lead to worse nasal and ear symptoms in the first post-operative week. Long-term, NSF do not affect quality of life after endoscopic skull base surgery. Abstract: Background: The endoscopic endonasal approach to the skull base avoids some of the surgical morbidity associated with a transcranial approach, however it often results in large skull-base defects requiring secure closure. The nasoseptal flap has become the preferred method for closure of such defects but may be associated with its own morbidity. Methods: A consecutive cohort of patients with skull base pathology with prospectively collected quality of life data using ASBQ and SNOT was analysed. They were grouped into those who received a nasoseptal flap and those who did not. Pre-operative total ASBQ and SNOT scores, and their individual components, were compared to data collected at days 1, 3, and 7; six-weeks; and 3, 6, and 12-months postoperatively. Results: Of 158 patients available for analysis, nasoseptal flaps were performed in 52 (33%). Average follow-up (±standard deviation) was 8.1 ± 3.9 months for ASBQ data and 8.2 ± 3.8 months for SNOT data. In the first post-operative week, nasal symptoms and otalgia were worse in the flap group. At six-weeks and beyond, there was no difference between groups in overall ASBQ or SNOT scores, or in the rate of clinically-significant improvement in SNOT or ASBQ scores or their components. Conclusion: In the largest cohort of patients to date, the use of a nasoseptal flap is associated with nasal symptoms and otalgia in the acute post-operative period, but is not associated with any long-term detriment to quality of life after endoscopic skull base surgery.